Lightweight high-elasticity modified EVA foaming material and preparation method and application thereof
By using branched polyolefin elastomer and maleic anhydride grafted EVA/POE as compatibilizers in EVA midsole materials, the problems of low rebound performance and large changes in low temperature hardness of EVA midsole materials are solved, and lightweight, high elastic, low compression permanent deformation and good low temperature performance are achieved.
Patent Information
- Application Number
- CN202411994584.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing EVA midsole material has low rebound performance, large compression and permanent deformation, and large hardness changes in low temperature environments, affecting the comfort and durability of the sole.
Branched polyolefin elastomer is used as a toughening agent, and branched polyolefin elastomer with long and short branched structures is prepared by solution polymerization, and maleic anhydride grafted EVA and POE are combined as compatibility agents to improve the compatibility and toughening properties of the material.
It significantly improves the room temperature and low temperature elasticity of foamed materials, reduces permanent compression deformation, reduces hardness changes at low temperatures, and improves the temperature application range and durability of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer foaming materials, and in particular relates to a lightweight and highly elastic modified EVA foaming material and a preparation method and application thereof. Background Art
[0002] Sports shoes include shoes used in various leisure sports and professional competitive sports. They protect the human foot and can improve the effect of sports to a certain extent. The structure of sports shoes includes textile uppers, insoles, midsoles and outsoles. The upper covers the foot, is comfortable and breathable, and provides a recognizable appearance. The outsole mainly prevents slipping and wear. The midsole is the core part of sports shoes, which is very technologically advanced, providing stability, cushioning and rebound for sports, absorbing the impact of sports, and providing energy feedback.
[0003] Existing midsole foaming substrates include Peba nylon elastomer (Polyeher block amide), TPEE thermoplastic polyester elastomers (Thermoplastic polyester elastomers), TPU thermoplastic polyurethane elastomers (Thermoplastic polyurethane elastomers) and EVA (Ethylene vinyl acetate) materials. Among them, the midsole shoe material based on TPU supercritical foaming was developed by Adidas and BASF. It has superior shoe material performance, high resilience and good durability, but it has a high density and is expensive. It currently accounts for about 5% of the market. Pebax nylon elastomer has the highest rebound performance (greater than 80%) and good impact resistance, but it is currently only produced by Arkema, with small output, few brands, high prices, and a small market share, which is limited to professional sports shoes. TPEE thermoplastic polyester elastomer has high tensile strength, low-temperature impact resistance, tear resistance, good durability, and high resilience; but it is expensive, and as an emerging shoe material, it has a small market production ratio. EVA-based foam materials are soft and cost-effective, and currently account for more than 90% of the market. However, their cushioning capacity is weak, and their resilience is small, about 40-50%. In addition, the soles tend to harden after repeated trampling. Therefore, the development of modified EVA midsole materials has strong practical significance and great market prospects.
[0004] At present, EVA midsole material modifiers include POE (Polyolefin elastomer), EPDM (EthylenePropylene Diene Monomer), and SEBS (Styrene Ethylene Butylene Styrene, hydrogenated styrene-butadiene-styrene block copolymer). Compared with EPDM, POE products are granular, eliminating the need for block rubber premixing. POE also has good processability, excellent mechanical properties, and good weather resistance. Compared with SEBS, POE has smaller thermal compression deformation and lower density.
[0005] POE modified EVA foam materials can be prepared by a variety of foaming processes, including compression chemical foaming, cross-linking injection foaming and supercritical foaming. The performance and formulation of foamed products are strongly correlated with the foaming process parameters. Deng Fuquan et al. (Functional Materials 4 (43), 2012, 508-511) explored the influence of the amount of foaming agent azodicarbonamide (AC), cross-linking agent diisopropylbenzene peroxide (DCP), talcum powder, etc. on the performance of POE / EVA composite foam materials. Cheng Bo et al. (Plastics 41 (4), 2012, 52-55) used chemical foaming to study the effect of POE on the foaming behavior and mechanical properties of EVA foam materials. The results show that with the increase of POE content, on the one hand, the elasticity of the foam material is increased, the compression permanent deformation is reduced, but the tensile and tear strength are reduced, and on the other hand, the pore diameter is reduced and the pore density is increased. As the content of POE-g-MAH increases, on the one hand, the tensile strength, tear strength and abrasion resistance of the foamed material are significantly improved, and on the other hand, the pore diameter is further reduced and the pore density is increased. Liu Wei (Plastics 48(5), 2019, 54-57) used supercritical CO2-assisted foaming to prepare POE / EVA composite foaming materials. By changing the ratio of POE / EVA, the effects of different proportions of POE / EVA on its macroscopic foaming ratio and microscopic morphology at the same foaming temperature and saturation pressure were studied. The results show that when the mass fraction of EVA added is 40%, the apparent density of the composite foaming material at a saturation pressure of 10MPa is 0.169g / cm3, and the foaming ratio is 5.3; its pore size is 56μm, and the pore density is 4.27×10 6 Pieces / cm 3 The pores have good microscopic morphology and uniform size. However, the resilience of EVA foam is still low. It is necessary to further improve its resilience, reduce its compression permanent deformation, and improve the durability of the material.
[0006] In addition, traditional EVA materials have a high glass transition temperature, and their hardness changes greatly under low temperature conditions, their rebound performance is greatly reduced, and their shock absorption performance becomes poor, resulting in poor comfort of the soles in low temperature environments and even easy breakage, which seriously affects the consumer experience.
[0007] Therefore, it is necessary to improve the low-temperature resilience performance of EVA foam materials, reduce the hardness change at low temperatures, and provide a low-temperature resistant, lightweight, and highly elastic modified EVA foam material. Summary of the invention
[0008] In view of this, the purpose of the present invention is to overcome the defects and shortcomings in the prior art and provide a lightweight and highly elastic modified EVA foam material modified by a branched polyolefin elastomer, which has significantly improved resilience compared with existing materials, reduced compression permanent deformation, and little change in low-temperature hardness, and is suitable for severe cold environments.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A lightweight and highly elastic modified EVA foam material comprises the following components in parts by weight:
[0011] Ethylene-vinyl acetate copolymer 50-90 parts
[0012] Branched polyolefin elastomer 10-50 parts
[0013] 2-5 parts of foaming agent
[0014] Foaming aid 0.5-2 parts
[0015] Crosslinking agent 0.5-2 parts
[0016] Lubricant 0.6~3 parts
[0017] Filler 1~30 parts
[0018] Compatibilizer 5 to 10 parts.
[0019] The branched polyolefin elastomer has a long and short branched chain structure, a weight average molecular weight of 20,000-8,000,000 g / mol, a branching degree of 50-120 / 1000C, and a melt index of 0.1-20 g / 10 min at 190°C and a load of 2.16 kg;
[0020] Furthermore, the branched polyolefin elastomer is one or more combinations of branched elastomers prepared by solution polymerization using ethylene or ethylene and C3-C5 olefins as raw materials. The branched polyolefin elastomer is preferably a single ethylene branched polymerization product.
[0021] Furthermore, the weight average molecular weight of the branched polyolefin elastomer is preferably 50,000 to 500,000 g / mol, the degree of branching is 60 to 90 / 1000C, and the melt index at 190°C and a load of 2.16 kg is 0.5 to 10 g / 10 min.
[0022] Furthermore, the branched polyolefin elastomer has a melting point in the range of 10°C to 90°C, preferably in the range of 10°C to 80°C.
[0023] The crystallinity is 1-20%, preferably 1-10%.
[0024] Preferably, the lightweight high-elastic modified EVA foam material comprises the following components in parts by weight:
[0025] Ethylene-vinyl acetate copolymer 50-70 parts
[0026] 30-50 parts of branched polyolefin elastomer
[0027] 2-5 parts of foaming agent
[0028] Foaming aid 0.5-2 parts
[0029] Crosslinking agent 0.5-2 parts
[0030] Lubricant 0.6~3 parts
[0031] Filler 1-10 parts
[0032] Compatibilizer 5 to 10 parts.
[0033] In the present invention, the branched polyolefin elastomer can be prepared by the following method:
[0034] Add an organic solvent, a catalyst and a co-catalyst into a reactor, control the temperature at 10-100° C., introduce ethylene into the reactor to carry out a polymerization reaction, the ethylene pressure is 0.1-5 MPa, the reaction time is 10-90 min, after the reaction is completed, add the reaction solution into acidified ethanol to terminate the reaction to obtain a solid precipitate, wash and dry the solid precipitate to obtain a branched polyolefin elastomer;
[0035] The catalyst is a late transition metal catalyst.
[0036] The late transition metal catalyst is a metal complex olefin polymerization catalyst with a late transition metal atom such as nickel (II), palladium (II), iron (II), cobalt (II), ruthenium (II) as the active center, and the chelated ligand is selected from the types of N^N, P^N, N^O, P^O, etc. All kinds of late transition metal catalysts disclosed in the prior art that can catalyze ethylene polymerization to prepare branched polyolefins and can obtain the defined parameters of the branched polyolefin material of the present invention can be applied to the present invention.
[0037] Furthermore, the late transition metal catalyst is a Brookhart catalyst, such as a (a-diimine) nickel / palladium complex, and more preferably an α-diimine nickel catalyst.
[0038] The cocatalyst is one or more of diethylaluminum monochloride, ethylaluminum dichloride, methylaluminoxane, polymethylaluminoxane, and ethylaluminum sesquichloride (EASC), preferably methylaluminoxane.
[0039] The molar ratio of Al in the co-catalyst to Ni in the α-diimine nickel catalyst is 50 to 1000:1.
[0040] The polymerization reaction is carried out in an organic solvent, and the organic solvent is one or more of dichloromethane, toluene and n-hexane.
[0041] In the present invention, a branched structure with adjustable length and short branched chain structures is obtained by long chain branching polymerization in a solution using a late transition metal catalyst. Since the present invention is an in-situ polymerization of ethylene, the branched chain contains long chains and short chains, has a high degree of branching, and the long branched chain increases the crosslinking point, has a low crystallinity, and improves the performance of the elastomer.
[0042] Furthermore, the compatibilizer is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE in a mass ratio of 1:0.1 to 2.
[0043] In the present invention, the content of VA in the ethylene-vinyl acetate copolymer is 12 to 30 mol%.
[0044] Furthermore, in the present invention, the blowing agent is AC blowing agent (azodicarbonamide).
[0045] The foaming aid is nano zinc oxide or nano zinc acetate. The particle size and distribution of the foaming aid will affect the decomposition temperature and gas volume of the foaming agent. Nano zinc oxide is commonly used.
[0046] The crosslinking agent is diisopropylbenzene peroxide (DCP) or di-tert-butyl peroxyisopropylbenzene (BIPB). BIPB is preferred. The decomposition temperature of BIBP is 10°C higher than that of DCP, and the dosage is about 2 / 3 of that of DCP. Moreover, the foamed product is odorless, meeting the increasingly stringent environmental protection requirements.
[0047] The lubricant is stearic acid.
[0048] The filler is calcium carbonate or talc.
[0049] The light and highly elastic modified EVA foam material is obtained by mixing the raw materials in proportion, mixing them into sheets, and then foaming them by molding.
[0050] The present invention also provides a method for preparing the lightweight high-elastic modified EVA foam material, which comprises:
[0051] Ethylene-vinyl acetate copolymer, branched polyolefin elastomer and compatibilizer are blended in an internal mixer at 105-120° C., and then a lubricant, a foaming promoter and a filler are added. After mixing, the temperature is lowered to 95-105° C., a foaming agent and a cross-linking agent are added, mixed, and pressed into sheets at 85-90° C. using an open mixer to obtain a sheet. After cutting into a suitable size, the sheet is molded and foamed in a flat vulcanizer to obtain the lightweight and highly elastic modified EVA foam material.
[0052] The blending time of the ethylene-vinyl acetate copolymer, the branched polyolefin elastomer and the compatibilizer is preferably 2-8 minutes, and the speed of the internal mixer is 40-50 r / min.
[0053] After adding the lubricant and foaming promoter, the blending time is preferably 2-8 minutes.
[0054] After adding the blowing agent and the cross-linking agent, the blending time is preferably 5-12 minutes.
[0055] Generally speaking, internal mixing and blending have better effects, and open mixing and melting temperature is easier to control. Melt blending can be done by internal mixing or open mixing, or by first internal mixing POE and EVA, and then mixing other components in an open mixing mill and producing sheets.
[0056] The thickness of the sheet is preferably 1 to 15 mm.
[0057] The sheet is preferably left to stand for 24 to 48 hours before being subjected to compression foaming.
[0058] In the method, the temperature of the compression foaming is generally 180-200° C., the pressure is 10-15 MPa, and the time is 10-12 minutes.
[0059] After the molding and foaming, the material is cooled and shaped, and then placed at room temperature for 24-48 hours to obtain the light and highly elastic modified EVA foam material.
[0060] In the present invention, the branched polyolefin elastomer has a high degree of branching, and still has a low melting temperature and crystallinity when the molecular weight increases, and has good toughening performance at both room temperature and low temperature. In addition, the present invention combines maleic anhydride grafted EVA and maleic anhydride grafted POE as compatibilizers, maleic anhydride grafted EVA and EVA have good compatibility, maleic anhydride grafted POE and POE have good compatibility, and both contain maleic anhydride grafting, and have similar polarity and good compatibility, thereby improving the compatibility of the overall melt of EVA and POE, so that the toughening performance of the branched polyolefin elastomer is further improved, and the resilience at room temperature can reach 60%, and the compression permanent deformation can be as low as 15%. In addition, the branched polyolefin elastomer has a large molecular chain entanglement and a low glass transition temperature, so it can significantly increase the low-temperature toughness of the foaming material, reduce the hardness change at low temperature, and improve the elasticity in a low-temperature environment. The resilience of the foaming material of the present application at -15°C can still reach more than 30%, and the hardness change is less than 10.
[0061] The light and highly elastic modified EVA foam material of the present invention can be used to prepare highly elastic and cold-resistant soles, and is particularly suitable for use in high-cold environments.
[0062] Compared with the prior art, the beneficial effects of the present invention are:
[0063] The present invention adds a branched polyolefin elastomer with a long and short branched chain structure as a toughening agent, which can effectively improve the toughening efficiency of the matrix and the filler loading effect, while allowing the composite material to maintain good processing stability and reduce the defect rate.
[0064] The present invention adopts light olefin raw materials and solves the technical problem that the toughening performance of ethylene-light olefin copolymer as elastomer is not as good as that of ethylene-octene copolymer by increasing the branching degree of elastomer. Compared with traditional POE ethylene-octene copolymer, the use of light olefin as raw material reduces the raw material cost and improves the economic benefit.
[0065] The present invention adopts a composite compatibilizer to improve the compatibility of the melt, further improve the toughening effect of the branched polyolefin elastomer, significantly improve the room temperature elasticity and low temperature elasticity of the foaming material, improve the comfort and durability of the sole, significantly reduce the hardness change of the foaming material at low temperature, increase the temperature application range of the material, and has great application and promotion value. DETAILED DESCRIPTION
[0066] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0067] The present invention is described in detail below in conjunction with embodiments.
[0068] Example 1
[0069] In 100 mL of n-hexane solvent, α-diimine nickel catalyst (2 μmol) and sesquiethylaluminum chloride (2 mmol, Al:Ni molar ratio=1000) were added, the temperature was controlled at 20-80° C., ethylene was introduced to carry out polymerization reaction, timing was started after the ethylene pressure was stable, the ethylene pressure was 0.1-5 MPa, the reaction time was 10-70 min, after the reaction was completed, the reaction solution was added to 200 mL of acidified ethanol, stirred for 10 h, filtered, washed with ethanol, and vacuum dried to obtain a branched polyolefin material;
[0070] The α-diimine nickel catalyst used in this embodiment is prepared according to the following reaction formula:
[0071]
[0072] In the formula I, R1 is phenyl or substituted phenyl, and the substituted phenyl is p-aminophenyl, p-methylphenyl, p-methoxyphenyl or p-tert-butylphenyl;
[0073] R2 is phenyl or substituted phenyl, wherein the substituted phenyl is p-methylphenyl, p-methoxyphenyl, p-fluorophenyl or p-tert-butylphenyl;
[0074] R3 is phenyl or substituted phenyl, wherein the substituted phenyl is p-methoxyphenyl, p-fluorophenyl or p-tert-butylphenyl;
[0075] In a toluene solvent, the aniline compound represented by formula II and diacetyl are mixed in a molar ratio of 2 to 2.2:1, and heated to 60 to 90°C for reaction for 20 to 24 hours under the action of a catalytic amount of p-toluenesulfonic acid. Then, the mixture is separated by water using a water separator and refluxed for 2 to 3 days to obtain a diimine ligand compound represented by formula III;
[0076] The diimine ligand compound shown in formula III and (DME)NiBr2 are mixed in a molar ratio of 1:0.5-2, dissolved in dichloroethane solvent, and stirred for reaction for 10-24 hours under nitrogen protection to obtain an α-diimine nickel catalyst shown in formula I.
[0077] In this embodiment, the α-diimine nickel catalyst in which R1, R2 and R3 are all p-tert-butylphenyl is prepared by the following specific method:
[0078] 2,4-di(p-tert-butylphenyl)-6-di-p-tert-butylphenyl methylaniline (4mmol) and diacetyl (2mmol) were dissolved in 100mL toluene, and 10mg of p-toluenesulfonic acid (PTSA) was added, and the mixture was stirred and refluxed at 80°C for 24h. Then, the mixture was refluxed for 3 days using a Dean-Stark water separator. After the reaction solution was cooled to room temperature, part of the solvent was evaporated under reduced pressure to precipitate a solid. 400mL of methanol was added to precipitate a solid product, which was filtered, and the filter cake was washed with methanol and dried to obtain a diimine ligand compound with a yield of 81%.
[0079] Under nitrogen protection, the diimine ligand compound and (DME)NiBr2 (0.2 mmol) and the diimine ligand compound (0.20 mmol) were mixed and dissolved in 5 mL of dichloromethane, stirred and reacted at room temperature for 20 hours, and dichloromethane was removed under reduced pressure and ether was added to precipitate a red solid, which was filtered, washed with ether, and dried to obtain an α-diimine nickel catalyst. The yield was about 85%
[0080] In 100 mL of n-hexane solvent, α-diimine nickel catalyst (2 μmol) and methylaluminoxane (2 mmol, Al:Ni molar ratio=1000) were added, the temperature was controlled at 20-80° C., ethylene was introduced to carry out polymerization reaction, timing was started after the ethylene pressure was stable, the ethylene pressure was 0.1-5 MPa, the reaction time was 10-70 min, after the reaction was completed, the reaction solution was added to 200 mL of acidified ethanol, stirred for 10 h, filtered, washed with ethanol, and vacuum dried to obtain a branched polyolefin elastomer;
[0081] With ethylene as raw material, n-hexane as solvent, α-diimine nickel catalyst as catalyst, methylaluminoxane as co-catalyst, by adjusting the ratio of main catalyst to co-catalyst, process and product compound combination, branched structure elastomer A (reaction temperature 30°C, pressure 0.5MPa, melt index 1.0g / 10min, molecular weight 350,000, branching degree 50 / 1000C, crystallinity 9%, melting point 72°C), elastomer B (reaction temperature 45°C, pressure 0.5MPa, melt index 5g / 10min, molecular weight 200,000, branching degree 70 / 1000C, melting point 61°C, crystallinity 5%) and elastomer C (reaction temperature 60°C, pressure 1.5MPa, melt index 0.2g / 10min, molecular weight 520,000, branching degree 115 / 1000C, melting point 10°C, crystallinity 1%) are prepared respectively.
[0082] Using ethylene and octene as raw materials, alkanes as solvents, and transition metal complex catalysts, by adjusting the main catalyst type, ratio, and process, a branched structure elastomer D (melting index 1.1 g / 10min, molecular weight 250,000, branching degree 45 / 1000C, crystallinity 15%, melting point 65°C) was obtained.
[0083] The EVA used in the embodiment is Elvax 265: VA molar content is 28%, DuPont.
[0084] The foaming agent is AC foaming agent, the foaming aid is nano zinc oxide, the crosslinking agent is BIPB, the lubricant is stearic acid, the filler is talcum powder, and the compatibilizer is a mixture of EVA-g-MAH and POE-g-MAH in a mass ratio of 1:0.5.
[0085] The formulas of Experiment No. 1 to 4 are shown in Table 1 below:
[0086]
[0087] The process for preparing the foaming material is as follows:
[0088] Use RM-200C mixing torque rheometer to mix POE, EVA and compatibilizer. The mixing parameters are as follows: temperature 105-120℃, rotation speed 40-50r / s, mixing time 8min; then add stearic acid, nano zinc oxide, talcum powder, blend for 5min, cool to 95-100℃, add AC foaming agent and BIPB, blend for 8min, after the mixing is completed, transfer the colloid to HTR-120 double-roll mill to mix the melt. The mixing parameters are: double-roll temperature 85-90℃, rotation speed 20-30r / s, and mixing time 5-10min. Make the blended system into 3mm thick sheets and leave them for at least one day after the sheets are produced;
[0089] The sheet is cut into suitable size, placed in a customized foaming mold, and put into a flat vulcanizer. The mold temperature is controlled at 180°C, the pressure is 12Mpa, and the time is 10 minutes. After cooling and shaping, it is placed at room temperature for 3-5 days before testing.
[0090] Performance characterization:
[0091] Resilience: Use HMLQ drop ball rebound tester, test standard: GB / T 6670-2008 Determination of rebound performance of soft foam polymer materials by drop ball method; the steps are as follows:
[0092] 1. Cut the product into a rectangle with a length and width of 100mm*100mm, a height of 50mm, and flat top and bottom;
[0093] 2. Place the sample on the reference surface, and adjust the distance from the bottom of the steel ball to the sample surface to 460 mm, and make sure there is light contact between the tube and the sample without causing any visible pressure;
[0094] 3. Place the steel ball on the release device, then release the steel ball and record the integer value of the maximum rebound height. If the ball hits the inner wall of the tube during the falling process or the rebound process, the test result is invalid. This happens mainly because the tube is not vertical or the surface of the sample is uneven. In order to reduce visual errors, the tester's line of sight should be in a horizontal straight line with the rebound reading scale on the tube. In order to prove the accuracy of the visual level, a test is necessary;
[0095] 4. The samples must obtain at least 3 valid rebound values within 1 minute;
[0096] 5. The results show that 3 results were obtained for each sample. If one value exceeds 20% (one fifth) of the median value, two more tests are conducted to determine the median value among the 5 values. From the median values of the 3 samples, the median value is taken as the sample's rebound rate;
[0097] Compression set: Use ASTM D3574 compression set tester; Test standard: GB / T 6669-2008 Determination of compression set of soft foam polymer materials; Test steps:
[0098] Here are the steps:
[0099] 1. The upper and lower surfaces of the specimen are flat, with a length and width of 50 mm and a thickness of 25 mm;
[0100] 2. Measure the initial thickness H0 of the sample;
[0101] 3. Place the sample between the two plates of the device, compress the sample by 50% of its thickness, and maintain this state;
[0102] 4. Within 15 minutes, place the compressed sample or the superimposed sample in an oven at 70°C and keep it for 22 hours;
[0103] 5. Take out the device from the oven and take out the sample from the device within 1 minute, and place it on the surface of a low thermal conductivity object (such as a wooden board). The surface temperature of the object should be the laboratory temperature.
[0104] 6. Measure the final thickness H of the specimen. Permanent compression set is deformation / initial thickness.
[0105] Hardness: Use MC010-LX-C microporous material hardness tester; test the microporous material hardness of shoes according to HG-T 2489-2007. Test steps:
[0106] 1. Raise the sample platform, so that the pressure foot of the hardness tester is in full contact with the sample platform under the action of the fixed weight. At this time, the value displayed should be 100. When the pressure needle completely leaves the sample platform, it should indicate 0;
[0107] 2. Place the sample on the sample platform, keep the pressure needle at least 10mm away from the edge of the sample, slowly raise the platform, and steadily and without impact, press the hardness tester to the sample under the action of the specified weight. When the pressure foot is in full contact with the sample and is subjected to the test load, read the value within 1s;
[0108] 3. Each measuring point can only be measured once, and there must be no less than three measuring points at different locations on the same sample that are more than 10 mm apart;
[0109] Tear strength: Tested using CMT5000 tensile testing machine; Tested according to GB / T 10808-2006 for the determination of tear strength of polymer porous elastic materials; Test steps:
[0110] 1. The thickness of the sample shall not be less than 24mm;
[0111] 2. Provide at least 5 samples for testing, and generally shall not be used for testing within 72 hours after production;
[0112] 3. The fixture moving speed is 50mm / min~500mm / min.
[0113] 4. Measure the thickness of the sample according to the position and direction in the figure (GB / T 10808-2006);
[0114] 5. Carefully unfold the test piece, place it on the fixture of the testing machine, adjust it to the appropriate position, and apply force to the test piece in the direction shown in the figure (GB / T 10808-2006);
[0115] 6. During the tearing process, if it is necessary to keep the cut of the sample in the center, a sharp knife can be used for auxiliary cutting, such as a single-sided razor.
[0116] 7. When the sample is torn to 25mm±5mm, record the maximum force value on the display or dial, and issue a report on the tear strength of three samples.
[0117] Density: Determination of apparent density of foam plastics and rubber according to GB / T 6343-2009.
[0118] Foaming ratio: density before foaming / density after foaming.
[0119] The performance test results of EVA foam materials made of four different elastic systems are shown in Table 2:
[0120]
[0121] The experimental results show that the elastomers used in experiments NO 1, 2, 3, and 4 have different branching degrees, but have little effect on the density and foaming ratio of the foaming material.
[0122] The degree of elastomer branching of experiments NO 1, 2, and 3 is higher than that of experiment NO 4. From the performance point of view, the room temperature resilience and low temperature resilience of experiments NO 1, 2, and 3 are significantly better than those of experiment NO 4, the compression permanent deformation is also smaller, and the increase in hardness at low temperature is also less than that of experiment No 4, which has better low temperature performance.
[0123] In addition, the degree of branching of the elastomer used in experiments NO 1, 2, and 3 is increased, the hardness at room temperature is reduced, but the resilience is increased, and the increase in low-temperature hardness is reduced, indicating that the increase in branching is beneficial to increasing the resilience and low-temperature performance of the foaming material.
[0124] The elastomer of Experiment NO 4 is an ethylene-octene copolymer, which has the lowest degree of branching among the four elastomers and is a commonly used POE elastomer. However, conventional POE elastomers have limited improvement on the resilience of foamed materials. The present invention adjusts the degree of branching of the elastomer and finds that the degree of branching is increased to above 50 / 1000C, which significantly improves the resilience of the foamed material. It is speculated that this may be because the ethylene copolymer elastomer of the present invention has long and short side chains, and the side chains form a curled winding structure, which has better toughness or elasticity.
[0125] Example 2
[0126] The formulas of Experiments NO 5-8 are shown in Table 3 below, and the preparation steps and test steps are the same as those of Example 1.
[0127]
[0128] The performance test results of the EVA foam materials of Experiments NO 5 to 8 are shown in Table 4:
[0129]
[0130]
[0131] The results in Table 4 show that in Experiment No. 5, no compatibilizer is added. Due to poor melt compatibility, resilience, low temperature performance and strength are all poor. In Experiments NO 6 and 7, EVA-g-MAH and POE-g-MAH are added as single compatibilizers, respectively. Among them, EVA-g-MAH has good compatibility with EVA, and has a higher toughening efficiency for the system, which is better than POE-g-MAH in Experiment NO 7. But overall, Experiment NO 8 uses a composite compatibilizer, and the overall performance is effectively improved. The present invention proposes for the first time that a composite compatibilizer is beneficial to improving the toughening efficiency of elastomers, and improving the resilience and low temperature performance of foaming materials.
[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lightweight and highly elastic modified EVA foam material, characterized in that: The composition comprises the following components in parts by weight: Ethylene-vinyl acetate copolymer 50-90 parts Branched polyolefin elastomer 10-50 parts 2-5 parts of foaming agent Foaming aid 0.5-2 parts Crosslinking agent 0.5-2 parts Lubricant 0.6~3 parts Filler 1~30 parts Compatibilizer 5-10 parts The branched polyolefin elastomer has a long and short branched chain structure, a weight average molecular weight of 20,000-8,000,000 g / mol, a branching degree of 50-120 / 1000C, and a melt index of 0.1-20 g / 10 min at 190°C and a load of 2.16 kg.
2. The lightweight and highly elastic modified EVA foam material according to claim 1, characterized in that The branched polyolefin elastomer is one or more combinations of branched elastomers prepared by solution polymerization using ethylene or ethylene and C3-C5 olefins as raw materials.
3. The lightweight and highly elastic modified EVA foam material according to claim 2, characterized in that The branched polyolefin elastomer is a single ethylene branched polymerization product.
4. The lightweight and highly elastic modified EVA foam material according to claim 1, characterized in that The branched polyolefin elastomer has a weight average molecular weight of 50,000 to 500,000 g / mol, a branching degree of 60 to 90 / 1000C, and a melt index of 0.5 to 10 g / 10 min at 190° C. and a load of 2.16 kg.
5. The lightweight and highly elastic modified EVA foam material according to claim 1, characterized in that The branched polyolefin elastomer has a melting point in the range of 10° C. to 90° C. and a crystallinity in the range of 1-20%.
6. The lightweight and highly elastic modified EVA foam material according to claim 1, characterized in that The branched polyolefin elastomer is prepared by the following method: Add an organic solvent, a catalyst and a co-catalyst into a reactor, control the temperature at 10-100° C., introduce ethylene into the reactor to carry out a polymerization reaction, the ethylene pressure is 0.1-5 MPa, the reaction time is 10-90 min, after the reaction is completed, add the reaction solution into acidified ethanol to terminate the reaction to obtain a solid precipitate, wash and dry the solid precipitate to obtain a branched polyolefin elastomer; The catalyst is a late transition metal catalyst.
7. The lightweight and highly elastic modified EVA foam material according to claim 1, characterized in that The compatibilizer is a mixture of maleic anhydride grafted EVA and maleic anhydride grafted POE in a mass ratio of 1:0.1-2.
8. The lightweight and highly elastic modified EVA foam material according to claim 1, characterized in that The foaming agent is AC foaming agent, the foaming aid is nano zinc oxide or nano zinc acetate; the crosslinking agent is dicumyl peroxide or di-tert-butyl peroxycumene; the lubricant is stearic acid; and the filler is calcium carbonate or talcum powder.
9. The method for preparing the lightweight high-elastic modified EVA foam material according to any one of claims 1 to 8, characterized in that The method is: Ethylene-vinyl acetate copolymer, branched polyolefin elastomer and compatibilizer are blended in an internal mixer at 105-120° C., and then a lubricant, a foaming promoter and a filler are added. After mixing, the temperature is lowered to 95-105° C., a foaming agent and a cross-linking agent are added, mixed, and pressed into sheets at 85-90° C. using an open mixer to obtain a sheet. After cutting into a suitable size, the sheet is molded and foamed in a flat vulcanizer to obtain the lightweight and highly elastic modified EVA foam material.
10. Use of the lightweight and highly elastic modified EVA foam material according to any one of claims 1 to 8 in the preparation of highly elastic and cold-resistant soles.
Citation Information
Patent Citations
High shock-absorbing ethylene-vinyl acetate rubber foam material for shoes and preparation method of material
CN104231419A
Novel purpose of random hyperbranched polyethylene
CN105622803A
Rubber composition, application to foam products and production method
CN108299744A
Shock absorbing pad manufacturing method and product for supplementing shock absorption of artificial turf
KR102583110B1
Cited By
EVA (Ethylene Vinyl Acetate) foaming sole material and preparation method and application thereof
CN120554745A